Development and Validation of a Core, Care, Cure, Based Therapeutic Framework for Psychosomatic Transitions in Dialysis (International Journal of Atharva, 2025)
Background: Patients undergoing haemodialysis for end-stage renal disease (ESRD) frequently encounter a range of psychosomatic challenges, including persistent anxiety, chronic fatigue, emotional instability, and diminished motivation. These symptoms not only affect their psychological well-being but also interfere with treatment adherence, social functioning, and overall quality of life. Despite the clinical focus on physiological parameters, the psychosomatic dimension of dialysis care remains under-addressed in conventional models. A structured, phase-specific therapeutic approach is essential to support patients across the continuum of dialysis care before, during, and after treatment sessions.Aim:  This study aimed to develop, implement, and validate a therapeutic framework based on the Core–Care–Cure model, designed to address psychosomatic transitions in dialysis patients through five targeted interventions.Methods: A descriptive research design guided the study, which was conducted in three phases. Phase I involved framework development through a comprehensive literature review and expert consultations. Phase II focused on the creation of an educational module and a protocol booklet tailored for clinical and academic use. Phase III involved validation by fifteen experts using the Item-Level Content Validity Index (I-CVI) and Scale-Level Content Validity Index (S-CVI).Results: The framework demonstrated strong content validity, with I-CVI scores ranging from 0.87 to 1.00 and an overall S-CVI of 0.94. Expert feedback highlighted the framework’s clarity, cultural relevance, and practical applicability in both clinical and educational settings. Conclusion: The validated Core–Care–Cure framework offers a structured, patient-centered model for managing psychosomatic challenges in dialysis care. Its multimodal interventions are adaptable for integration into nursing education, clinical protocols, and psychosomatic support programs, contributing to holistic healing and improved patient outcomes.